2013
DOI: 10.1302/0301-620x.95b10.31222
|View full text |Cite
|
Sign up to set email alerts
|

Neurological deterioration due to missed thoracic spinal stenosis after decompressive lumbar surgery

Abstract: There have been a few reports of patients with a combination of lumbar and thoracic spinal stenosis. We describe six patients who suffered unexpected acute neurological deterioration at a mean of 7.8 days (6 to 10) after lumbar decompressive surgery. Five had progressive weakness and one had recurrent pain in the lower limbs. There was incomplete recovery following subsequent thoracic decompressive surgery. The neurological presentation can be confusing. Patients with compressive myelopathy due to lower thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 14 publications
2
47
0
1
Order By: Relevance
“…Hyperreflexia in the lower extremities is masked by the coexistence of LCS; thus, a thoracic lesion is easily overlooked, because surgeons can be deceived by the imaging findings of the lumbar lesion. Failure to detect thoracic lesions in patients presenting predominantly with LCS may be associated with a significant risk of injury to the spinal cord during positioning for lumbar Eur Spine J decompression surgery [7]. Since 88 % (44/50) of the thoracic lesions developed in the lower thoracic spine, careful attention should be paid to these areas on MRI and myelography in LCS patients to avoid missing thoracic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperreflexia in the lower extremities is masked by the coexistence of LCS; thus, a thoracic lesion is easily overlooked, because surgeons can be deceived by the imaging findings of the lumbar lesion. Failure to detect thoracic lesions in patients presenting predominantly with LCS may be associated with a significant risk of injury to the spinal cord during positioning for lumbar Eur Spine J decompression surgery [7]. Since 88 % (44/50) of the thoracic lesions developed in the lower thoracic spine, careful attention should be paid to these areas on MRI and myelography in LCS patients to avoid missing thoracic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, this syndrome is known as disseminated spinal canal stenosis, which is diffuse spinal canal stenosis through the cervical spine to the lumbar spine with at least two lesions [5]. In disseminated spinal canal stenosis, it is difficult to determine which level is most involved during the preoperative diagnosis [6,7]. In patients with clinical signs of CM, such as clumsiness of the hands and gait spasticity, diagnosis of associated TM is difficult since we cannot discriminate the symptoms of the lower extremities between CM and TM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the published data, the variety of clinical symptoms typical of the tandem compression of the spinal cord and cauda equin can lead to incomplete diagnosis (2,3,7). In these cases, the detection of the thoracic compression can be omitted due to different factors:…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have shown that asymptomatic thoracic stenosis is present in approximately 30% of patients undergoing lumbar decompressive surgery with the potential for significant impairment if missed [26].…”
Section: Clinical Evaluationmentioning
confidence: 99%